Comparative Genomics and Metabolomics Analyses of Clavulanic Acid-Producing Streptomyces Species Provides Insight Into Specialized Metabolism - AbuSara, Nader F.; Piercey, Brandon M.; Moore, Marcus A.; Shaikh, Arshad Ali; Nothias, Louis-Félix; Srivastava, Santosh K.; Cruz-Morales, Pablo; Dorrestein, Pieter C.; Barona-Gómez, Francisco; Tahlan, Kapil (Frontiers in Microbiology, 2019)
Clavulanic acid is a bacterial specialized metabolite, which inhibits certain serine β-lactamases; enzymes that inactivate β-lactam antibiotics to confer resistance. Due to this activity, clavulanic acid is widely used in combination with penicillin and cephalosporin (β-lactam) antibiotics to treat infections caused by β-lactamase producing bacteria. Clavulanic acid is industrially produced by fermenting Streptomyces clavuligerus, as large-scale chemical synthesis is not commercially feasible. Other than S. clavuligerus, Streptomyces jumonjinensis and Streptomyces katsurahamanus also produce clavulanic acid along with cephamycin C, but information regarding their genome sequences is not available. In addition, the Streptomyces contain many biosynthetic gene clusters thought to be “cryptic,” as the specialized metabolites produced by them are not known. Therefore, we sequenced the genomes of S. jumonjinensis and S. katsurahamanus, and examined their metabolomes using untargeted mass spectrometry along with S. clavuligerus for comparison. We analyzed the biosynthetic gene cluster content of the three species to correlate their biosynthetic capacities, by matching them with the specialized metabolites detected in the current study. It was recently reported the S. clavuligerus can produce the plant associated metabolite naringenin, and we describe more examples of such specialized metabolites in extracts from the three Streptomyces species. Detailed comparisons of the biosynthetic gene clusters involved in clavulanic acid (and Cephamycin C) production were also performed and based on our analyses, we propose the core set of genes responsible for producing this medicinally important metabolite.